Osteoclastogenesis-Related Cytokines and Peri-Prosthetic Osteolysis in Revision Metal-On-Metal Total Hip Replacements: The Work Was Presented at the 11th European Hip Society Congress; October 11, 2014, Stockholm, Sweden. Awarded Prize for Best Oral Presentation. Issue 4 (July 2015) - Eastwood, Sarah E.; John, Alun; Jones, Stephen A.; Hodgson, Helen; Mason, Deborah; Waddington, Rachel; Wei, Xiaoqing
Purpose: Peri-prosthetic osteolysis is a major cause for revision hip arthroplasty; various cytokines including those in the osteoclastogenesis pathway have been identified as potentially key in the osteolysis process. Adverse reactions to metal debris in metal-on-metal total hip replacements have led to an increase in revision procedures. This study examines the levels of osteoclastogenesis-related cytokines in serum and synovial fluid samples obtained from patients at the time of revision metal-on-metal total hip replacement and compares between patients with and without radiographic evidence of peri-prosthetic osteolysis. Methods: Sandwich ELISA techniques were used to detect IL-6, IL-18, M-CSF, sRANKL and OPG in the samples. Results were analysed with linear regression, Fisher's tests and t -tests; p<0.05 considered significant. Samples from 36 patients (18 with osteolysis, 18 without osteolysis) were analysed. Results: There was wide variation in the detectable levels of cytokines. No significant differences were found between patients with and without osteolysis in mean synovial fluid levels of IL-6 (p = 0.863), IL-18 (p = 0.324), M-CSF (p = 0.508), sRANKL (p = 0.884), OPG (p = 0.776) or mean serum levels of OPG (p = 0.993) or sRANKL (p = 0.565) (insufficient detection of IL-6, IL-18 or M-CSF in serum samples). A correlation was found between synovial fluid levels of IL-6 and OPG in patients without osteolysis (r 2 = 0.618, p<0.001) but not with osteolysis (r 2 = 0.0004). Conclusions: These results indicate that the process of peri-prosthetic osteolysis is complex and multifactorial; there may also be an influence of metallosis. Further research is needed to increase understanding of peri-prosthetic osteolysis and influence clinical practice.